Case Analyses for Abnormal Psychology / Learning to Look Beyond the Symptoms - Lafuze Joan; Osborne Randall E; Perkins David (Psychology Press - Taylor & Francis Group, 2000)
This casebook provides rich, detailed examples of the major mental illnesses. Acknowledgements, Preface, Introduction, Major Perspectives and the Assumptions Each Makes about Human Behavior, Diagnostic Interviews: The Importance of Critical Thinking in the Clinical Process, Classification and Diagnosis, The Case of Ricky G: Schizophrenia, The Case of Barbara M: Bipolar Disorder, The Case of Sally W.: Borderline Personality Disorder, The Case of Margaret H: Obsessive-Compulsive Disorder, The Case of Jacob T: Autism, The Case of Sarah Q: Bulimia Nervosa, The Case of Latisha Q: Panic Disorder, The Case of Richard B: Alcohol Addiction, The Case of Paula H: Post-Traumatic Stress Disorder, The Case of Brigid C: Dissociative Identity Disorder, Wrapping Up the Journey, References, Index.